Gender-based violence against women in the European Court of Human Rights: a case study on separate judicial opinions - Giordano, Ilaria; Zottola, Angela (Comparative Legilinguistics, 2025)
Far from being neutral and objective, the law often perpetuates existing prejudices – particularly gender stereotypes – which hinder equality and human rights. Despite recent efforts by bodies like the European Court of Human Rights (ECtHR) to condemn discriminatory legal language, such stereotypes persist, especially in contexts where domestic violence against women is still widespread and rooted in cultural norms: these narratives trivialise victims’ experiences and weaken legal protections, sustaining cycles of silence and fear. Against this backdrop, we examine cases of gender-based violence presented to the ECtHR from 2012 to 2024, and we specifically focus on separate opinions, which contest majority understandings of discriminatory or abusive acts and reveal competing judicial narratives. Following Ädel and Garretson’s (2006) taxonomy, we begin by analysing intertextuality to trace how judges cite, attribute or mention external and internal sources: this focus will reveal how dissenting voices engage with, resist or reinterpret dominant legal discourses, therefore exposing the systemic nature of injustice, or, conversely, reproducing harmful narratives. On this basis, we then move to the examination of a number of harmful discursive practices, i.e., argumentative or rhetorical choices that ideologically frame cases and contribute to the reproduction of gender-based violence. This qualitative analysis situates our findings within the framework of Feminist Critical Discourse Analysis (Lazar, 2005), which explores how discourse sustains or challenges hierarchies of gendered power.